Sonochemical-assisted magnesium borate synthesis from different boron sources - Yildirim, Meral; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (DE GRUYTER POLAND SP ZOO, 2017)
In this study, sonochemical-assisted magnesium borate synthesis is studied from different boron sources. Various reaction parameters are successfully applied by a simple and green method. X-ray diffraction (XRD), Fourier transform infrared (FT-IR) and Raman spectroscopies are used to characterize the synthesized magnesium borates on the other hand surface morphologies are investigated by using scanning electron microscope (SEM). The XRD analyses showed that the products were admontite [MgO(B2O3)(3). 7(H2O)] with JCPDS (Joint Committee on Powder Diffraction Standards) no. of 01-076-0540 and mcallisterite [Mg-2(B6O7(OH)(6))(2). 9(H2O)] with JCPDS no. of 01-070-1902. The results that found in the spectroscopic studies were in a good agreement with characteristic magnesium borate bands in both regions of infra-red and visible. According to SEM results, obtained borates were in micro and sub-micro scales. By the use of ultrasonication, reaction yields were found between 84.2 and 97.9%. As a result, it is concluded that the sonochemical approach is a practicable synthesis method to get high efficiency and high crystallinity in the synthesis magnesium borate compounds.
Keywords: magnesium borate; sonochemistry; spectroscopic analysis; ultrasonifi cation; XRD; THERMAL-CONVERSION; ULTRASOUND; NANOWHISKERS; CHEMISTRY; NANORODS; ROUTE; NANOPARTICLES; NANOMATERIALS; LINK; Engineering